UPAYA AMERIKA SERIKAT DALAM PERLINDUNGAN HAK ATAS KEKAYAAN INTELEKTUAL DI TIONGKOK MELALUI USTR - Ramadhan, Lazuardi Aditya; Wiranata, I Made Anom; Priadarsani, Ni Wayan Rainy (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRAK The piracy of US products in China has caused economic loss to business sector in the US. In responding the issue, the US Goverment formed USTR as the US trade representative abroad. The obligation and responsibility is to monitor US company investment and report IPR violation overseas. This US found that China is not consistent with its commitments to the WTO membership. This study aims to describe the efforts made USTR in protecting the nationalinterest of the US in China regarding of IPR protection from 2007 until 2009. This study was using qualitative descriptive method and the concept of national interest, coercive diplomacy, foreign policy and the protection of intellectual property rights. This research found that the USTR has made efforts to negotiate, evolution, control, and monitoring the problems of piracy of US products in China. Keywords: USTR, US, Chinese, IPR